Seeking Intersection of Religions: An Alternative Solution to Prevent the Problem of Religious Intolerance in Indonesia - Nur Chanifah; Arif Mustapa (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
Indonesia consisted of multiculture, ethnic and religion. There are six legal religions in Indonesia. Religious plurality is part of Indonesian life. In Religion, adherents always tried to compare between their own religion with other religions that can cause a truth claim of superiority of their religion. This caused any conflict like the case of GKI Yasmin in Bogor, three massive bomb blasts of Bali, and conflict of Ambon.  This is a library reseach applying sociological approach. To analyze the problem, author used the conflict theory of Gillin and Gillin saying that conflict can be caused by deferences. Therefore, it is necessary to understand how the intersection of religions in order to prevent the conflict, included religious intolerence.  This research find that the intersection of religion can be found in values of humanity or the horizontal aspect (ḥabl  min al-nās). While the vertical aspect (ḥabl  min Allāh), they are different. By understanding the intersection of religions and nature of these differences, it is expected that religious harmony can be reinforced.